Replication of the Self-Concept and Identity Measure (SCIM) Among a Treatment-Seeking Sample. Issue 1 (2nd January 2019) - Kaufman, Erin A.; Puzia, Megan E.; Crowell, Sheila E.; Price, Cynthia J.
ABSTRACT: Identity distress occurs within a variety of psychiatric conditions. Reliable tools for assessing identity-related functioning among clinical populations are greatly needed. The Self-Concept and Identity Measure (SCIM) is a brief self-report scale designed to assess healthy and disturbed identity dimensions. This measure has been validated within normative but not treatment-seeking samples. The present study used an a priori confirmatory approach to replicate the SCIM's factor structure among disadvantaged women enrolled in treatment for chemical dependence ( N = 216). The original three-factor structure and item loadings generally replicated within this diagnostically diverse, significantly impaired sample. Higher SCIM scores were also associated with other problems, such as emotion dysregulation and depression. Results support the SCIM's use and scoring with clinical populations.